Correlates of secondhand smoke exposure in public and private settings in Mexico. Encodat 2016 - Luis Zavala-Arciniega; Daniela Sarahí Gutiérrez-Torres; Wayra Citlali Paz-Ballesteros; Luz Myriam Reynales-Shigematsu; Nancy L Fleischer (Instituto Nacional de Salud Pública, 2019)
Objective. To assess the correlates of secondhand smoke exposure (SHS) in public and private settings. Materials and methods. Data came from the 2016 National Survey of Drug, Alcohol and Tobacco use. Multilevel Poisson models were conducted to evaluate factors associated with SHS. Results. Having a higher education, being male and being a young adult were associated with higher SHS in bars and restaurants. Men had greater SHS at work, while women and adolescents had greater exposure at home. Adults older than 45 years had higher SHS on public transportation compared to adolescents between 12-17 years old. Conclusions. Exposure to SHS remains high and affects the population differentially. To reduce SHS, it is necessary to apply Article 8 of the Framework Convention on Tobacco Control.